(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The use of panavir in the complex of etiopathogenetic therapy of patients with chronic bacterial prostatitis in combina tion with metabolic syndrome statistically significantly improves the results of treatment of chronic prostatitis, indicators of lipid metab olism, increases the fertility of the ejaculate. There were no adverse reactions to the drug. Should include panavir in the standard of therapy for patients with chronic bacterial prostatitis.